Forcings, Feedbacks, and Climate Sensitivity in HadGEM3‐GC3.1 and UKESM1. (17th December 2019) - Andrews, Timothy; Andrews, Martin B.; Bodas‐Salcedo, Alejandro; Jones, Gareth S.; Kuhlbrodt, Till; Manners, James; Menary, Matthew B.; Ridley, Jeff; Ringer, Mark A.; Sellar, Alistair A.; Senior, Catherine A.; Tang, Yongming
Abstract: Climate forcing, sensitivity, and feedback metrics are evaluated in both the United Kingdom's physical climate model HadGEM3‐GC3.1 at low (‐LL) and medium (‐MM) resolution and the United Kingdom's Earth System Model UKESM1. The effective climate sensitivity (EffCS) to a doubling of CO2 is 5.5 K for HadGEM3.1‐GC3.1‐LL and 5.4 K for UKESM1. The transient climate response is 2.5 and 2.8 K, respectively. While the EffCS is larger than that seen in the previous generation of models, none of the model's forcing or feedback processes are found to be atypical of models, though the cloud feedback is at the high end. The relatively large EffCS results from an unusual combination of a typical CO2 forcing with a relatively small feedback parameter. Compared to the previous U.K. climate model, HadGEM3‐GC2.0, the EffCS has increased from 3.2 to 5.5 K due to an increase in CO2 forcing, surface albedo feedback, and midlatitude cloud feedback. All changes are well understood and due to physical improvements in the model. At higher atmospheric and ocean resolution (HadGEM3‐GC3.1‐MM), there is a compensation between increased marine stratocumulus cloud feedback and reduced Antarctic sea‐ice feedback. In UKESM1, a CO2 fertilization effect induces a land surface vegetation change and albedo radiative effect. Historical aerosol forcing in HadGEM3‐GC3.1‐LL is −1.1 W m −2 . In HadGEM3‐GC3.1‐LL historical simulations, cloud feedback is found to be less positive than in abrupt‐4xCO 2, in agreement with atmosphere‐only experiments forced with observed historical sea surface temperature and sea‐ice variations. However, variability in the coupled model's historical sea‐ice trends hampers accurate diagnosis of the model's total historical feedback. Plain Language Summary: A new generation of climate models—called HadGEM3‐GC3.1 and UKESM1—have been developed in the United Kingdom and will be used widely in the Coupled Model Intercomparison Project Phase 6 (CMIP6). Evaluating the models' benchmark climate sensitivity and feedback metrics is a useful first step to understanding their characteristic response to forcing. The effective climate sensitivities are found to be higher than that seen in the previous generation of models, in common with other recently developed climate models. Reasons for this are discussed. Key Points: HadGEM3‐GC3.1 and UKESM1 have climate sensitivities of 5.5 and 5.4 K, respectively Our models' forcing and feedback processes are not atypical of models in general The relatively large climate sensitivity arises from an unusual combination of forcing and feedback